Co-rumination buffers the link between social anxiety and depressive symptoms in early adolescence - Van,Zalk N; Tillfors,M (Child and Adolescent Psychiatry and Mental Health, 2017)
ObjectivesWe examined whether co-rumination with online friends buffered the link between social anxiety and depressive symptoms over time in a community sample.MethodsIn a sample of 526 participants (358 girls; M age = 14.05) followed at three time points, we conducted a latent cross-lagged model with social anxiety, depressive symptoms, and co-rumination, controlling for friendship stability and friendship quality, and adding a latent interaction between social anxiety and co-rumination predicting depressive symptoms.ResultsSocial anxiety predicted depressive symptoms, but no direct links between social anxiety and co-rumination emerged. Instead, co-rumination buffered the link between social anxiety and depressive symptoms for adolescents with higher but not lower levels of social anxiety.ConclusionsThese findings indicate that co-rumination exerted a positive influence on interpersonal relationships by diminishing the influence from social anxiety on depressive symptoms over time.